On the Boundary Value Problem with the Operator in Boundary Conditions for the Operator-Differential Equation of the Third Order - Aliev, A.R.; Babayeva, S.F. (Журнал математической физики, анализа, геометрии, 2010)
A boundary value problem for a class of the operator-di®erential equations of the third order on a semi-axis, where one of the boundary conditions is perturbed by some linear operator, is studied. There are obtained su±cient conditions on the operator coe±cients of the considered boundary value problem providing its correct and univalent resolvability in Sobolev type space.